2022
DOI: 10.3390/polym14152985
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses in Adsorption Mechanism, Architectures, Electrode Materials and Applications for Advanced Electrosorption System: A Review

Abstract: As an advanced strategy for water treatment, electrosorb technology has attracted extensive attention in the fields of seawater desalination and water pollution treatment due to the advantages of low consumption, environmental protection, simplicity and easy regeneration. In this work, the related adsorption mechanism, primary architectures, electrode materials, and applications of different electrosorption systems were reviewed. In addition, the developments for advanced electrosorb technology were also summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 106 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…Taking the 60 min at which the time of the adsorption process begins to decrease toward the difference as the assumed endpoint of adsorption, most of the adsorption process is completed within 20 min of the beginning of adsorption, and this trend increases as the pole-plate spacing approaches 3 mm. 8 , 17 , 22 The adsorption behavior starts with more adsorption sites on the surface of the activated carbon fiber mat, and the adsorption moves faster toward the equilibrium, as the adsorption process goes on, the number of sites on the surface of the activated carbon fiber mat gradually decreases and finally approaches the equilibrium, and the adsorption capacity no longer changes significantly. The comparison between the different electrode spacing groups demonstrated that the 3 mm electrode spacing had a significant advantage in relative adsorption of 23.14 mg/g and differed significantly from the other spacing configurations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking the 60 min at which the time of the adsorption process begins to decrease toward the difference as the assumed endpoint of adsorption, most of the adsorption process is completed within 20 min of the beginning of adsorption, and this trend increases as the pole-plate spacing approaches 3 mm. 8 , 17 , 22 The adsorption behavior starts with more adsorption sites on the surface of the activated carbon fiber mat, and the adsorption moves faster toward the equilibrium, as the adsorption process goes on, the number of sites on the surface of the activated carbon fiber mat gradually decreases and finally approaches the equilibrium, and the adsorption capacity no longer changes significantly. The comparison between the different electrode spacing groups demonstrated that the 3 mm electrode spacing had a significant advantage in relative adsorption of 23.14 mg/g and differed significantly from the other spacing configurations.…”
Section: Resultsmentioning
confidence: 99%
“…It indicates that the mass transfer capacity of the electrosorption process gradually increases with the increase of voltage, bringing about the increase of adsorption amount, but the continued increase of voltage will bring about the side reaction of electrolytic water to produce a large number of micro-foam bubbles, which will encroach on a large number of adsorption sites and destroy the double electric layer structure, resulting in the da of relative adsorption amount. 8 , 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion cloud close to the solid surface forms the stern and diffuse layers, referred to as the Gouy-Chapman layers [71]. The oppositely charged ions are attracted to the surface of the solid and form the stern layer.…”
Section: Flocculationmentioning
confidence: 99%